(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article discusses what has been accomplished thus far in the field of digital financial inclusion in India, as well as how we can leverage modern technologies to create a more inclusive society by employing a variety of digital drivers. This article discusses the obstacles and challenges that prevent the realization of a digitally inclusive society. This article discusses the growth of E-commerce-enabled financial inclusion. It deconstructs the trends and key players that support them, identifies the adoption barriers, and makes recommendations for addressing the major issues, emphasizing the importance of interaction and transparency among all key stakeholders in order to establish a digitally inclusive ecosystem and make India’s next wave of digital financial inclusion more successful and accessible.